Longitudinal analysis of pediatric distal radius alignment parameters in a cohort of serial radiographs - Knapik, Derrick M.; Kolaczko, Jensen G.; Drummond, Ian; Liu, Raymond W. (Clinical anatomy (New York, N.Y.), 2021)
Background Growth in pediatric patients necessitates changes to bony structures throughout the entire body to suit development. Changes in the distal radius during growth are of interest in the pediatric population due to the high incidence of fractures. The purpose of this study was to assess for trends in three radiographic measurements (height of the radial styloid process, radial inclination, ulnar variance) of the distal radius using serial radiographs in subjects aged between 6 and 14 years of age. Materials and Methods Longitudinal radiographs from 68 healthy children (n = 34 males, 34 females) with a minimal of three annual radiographs between 6 and 14 years of age were analyzed. Measurements of height of the radial styloid process, radial inclination, and ulnar variance were performed in each available radiograph. Repeated measures analysis of variance (ANOVA) was performed to measure the association between alignment values and subject age. Results A total of 436 images in 68 subjects were analyzed, comprising a mean of 6.5 ± 2.0 radiographs per subject. Repeated measures ANOVA demonstrated that all measurement variables changed significantly with age (p < .001). Ulnar variance demonstrated the most variability with negative ulnar variance in younger children, and trends towards a more neutral ulnar variance by approximately 7 years in females and 11 years in males, while height of the radial styloid process and radial inclination changed relatively minimally with development. Conclusions In the adolescent age range, ulnar variance, height of the radial styloid process and inclination are all relatively stable and adult parameter values can be used to judge restoration of distal radius alignment.